Modesty in Learning Teacher of 3rd State School Sinaboi District at Rokan Hilir Regency - Sinaga, Mangatur; Charlina, Charlina; Septyanti, Elvrin; Ayu Pertiwi, Tri Yuliana (Proceedings of the UR International Conference on Educational Sciences, 2018)
This study describes the language fluency of teachers of SMP Negeri 3, Sinaboi District, Rokan Hilir Regency in learning. This research is a qualitative descriptive study. The object of this study is the teachers speech in the learning process. The theory used is pragmatic, based on the context of the follow-speech utterances, and politeness based on the premise Leech who viewed politeness from the standpoint of the hearer and not from the viewpoint of the speaker based on six maxims of politeness. The results showed that the speech teacher at SMP Negeri 3 Sinaboi District of Rokan Hilir in learning shows (1) the maxim of wisdom, that teachers are always (a) reducing the profit himself and (b) to maximize the advantages of students in learning activities; (2) the maxim of generosity (generosty maxim), namely the teacher respects students; (3) the maxim of appreciation, namely the teacher (a) does not mock, (b) interrupts each other, or (c) does not demean students; (4) the maxim of simplicity or humility, that is, the teacher is humble by reducing praise for oneself; (5) the maxim of agreement, namely teachers to foster compatibility with the students, and (6) kesimpatisan maxim, namely teachers maximize sympathy to their students.